Pembelajaran Menggunakan Modul Elektronik Berbasis Konstruktivisme Pada Jenjang Pendidikan Tinggi - Badrus Sholeh; Sholeh Hidayat; Ujang Jamaludin (LPPM Institut Pendidikan Nusantara Global, 2026)
The digitisation of education, particularly the creation of digital learning resources in the form of electronic modules, is one approach to adapting to the changes brought about by technological breakthroughs. The objective of this study is to determine the impact of constructivism-based electronic module learning at the higher education level. A literature review methodology was employed in this study. Articles published between 2020 and 2026 were used as data sources. The results of the study indicate that learning at the higher education level using constructivism-based electronic modules has the following effects: 1) Enhancing learning autonomy, 2) Increasing student motivation, 3) Improving understanding of abstract concepts, 4) Improving student learning outcomes, and 5) Increasing engagement in learning. Keywords: learning, electronic modules, constructivism theory, higher education